Ore Petrography, Carbonate Alteration and Geochemistry of the McBean Mine, Larder Lake, Ontario - Bell, Cameron (My University, 1987)
The McBean Mine is a small gold producer located along the Larder Lake Break. Ore from the open pit consists of massive and gneissic syenite. The highest go I d grades come from highly carbonitized syenitic rocks with abundant fine grained, euhedral pyrite. Petrographic observation shows gold to be found as inclusions in pyrite, platings on pyrite and as free grains in the gangue. XRD analyses show the major carbonate type to be dolomite. In addition to dolomite, minor amounts of calcite are found in auriferous syenitic rocks. SEM microscopy shows carbonate composition to vary with rock types and grain location. Geochemical studies show a high intensity of carbonate alteration and the association of gold with tungsten and uranium. Auriferous syenites were determined to have elevated HREE element abundances compared with unaltered syenite. The mine is therefore characterized by extensive hydrothermal carbonate alteration related to the Larder Lake Break.
Keywords: ore petrography; carbonate alteration; geochemistry; McBean Mine; geology